Implementasi Etika Bisnis Islami Bagi Pengusaha Terhadap Pelanggan Di Toko Seragam Sekolah di Pusat Grosir Butung Makassar - St. Atirah; Rusdiawan Rusdiawan (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2019)
This study aims to determine the application of Islamic business ethics values and the impact felt by school uniform entrepreneurs when implementing Islamic business ethics in their business. There are several principles in Islamic business ethics which consist of the principles of Tawheed, the Principles of Siddiq (Honesty), the principles of Amanah (Trust), the Principles of Tablig, and the principle of Fathanah (Intelligence). The result of this study is that Business Ethics in the Butung Wholesale Market Center environment is not fully in accordance with Islamic Sharia. Traders still give blank notes to customers who ask for harm to others, but out of that, the principles applied by businessmen at Butung Wholesale Center have fulfilled the nature that God and His Messenger implanted. As for what is included in Islamic Business Ethics include the Tauhid Principle which is channeled through zakat expenditure and trade sincerity, the Shiddiq Principle is reflected in the attitude of traders who do not multiply prices in buying and selling, and provide freedom for buyers to choose. The principle of Amanah, in the form of achieving optimal service as a form of gratitude to consumers. The Tabligh principle applied by traders includes communicating with friendliness, and establishing friendship with business partners and consumers. The Fathanah principle is reflected in its intelligence in acquiring and retaining customers.